Development Strategy of Jumog Waterfall as a Tourist Attraction in Karanganyar Regency, Central Java - Rahmawati Rahmawati; Hanugrah Kristiono Liestiandre; Matius Tinna Sarira; Hastuti Nurhayati; Faradila Anggun Surya Rini (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
This study focuses on the development strategies of Jumog Waterfall as a tourist attraction in Berjo Village, Ngargoyoso District, Karanganyar Regency, Central Java. Known as the "Lost Paradise," Jumog Waterfall offers a unique natural appeal with its pristine water sourced directly from Mount Lawu. The main objectives of this research are to identify the tourism potential of the waterfall, analyze the challenges faced by the local community in developing the site, and propose strategies for sustainable development. The research employs a qualitative approach, incorporating observational studies and semi-structured interviews with various stakeholders, including local residents, tourism managers, and visitors. The findings reveal that Jumog Waterfall possesses significant tourism potential due to its natural beauty, accessible facilities, and the active involvement of the local community. However, the development of this site is hindered by issues such as land ownership disputes, insufficient government support in training local entrepreneurs, and a lack of distinctive local products that could enhance the tourist experience. The study suggests that collaboration between the local government and the community is crucial to overcoming these challenges. Recommended strategies include improving infrastructure, offering training programs for local businesses, enhancing promotional efforts through digital platforms, and developing unique local products that reflect the cultural heritage of the area. This research contributes to the broader discourse on sustainable tourism development in rural areas and underscores the importance of community participation in managing and preserving natural attractions. The findings are expected to inform policymakers and stakeholders involved in the tourism sector, ultimately fostering economic growth and improving the quality of life for the residents of Berjo Village.